2011
DOI: 10.2176/nmc.51.679
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Fasudil in Patients With Subarachnoid Hemorrhage: Final Results of a Randomized Trial of Fasudil Versus Nimodipine

Abstract: Fasudil is believed to be at least equally effective as nimodipine for the prevention of cerebral vasospasm and subsequent ischemic injury in patients undergoing surgery for subarachnoid hemorrhage (SAH). We report the final results of a randomized, open trial to compare the efficacy and safety of fasudil with nimodipine. A total of 63 patients undergoing surgery for SAH received fasudil and 66 received nimodipine between 1998 and 2004. Symptomatic vasospasm, low density areas on computed tomography (CT), clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 22 publications
0
56
0
2
Order By: Relevance
“…With MDA significantly increased after SCI, SOD significantly reduced, suggesting that lipid peroxidation in damage localization increased, it is also the result of increased free radicals (Gonzalez et al, 2003;Wang et al, 2009;Hakan et al, 2011). Free radicals and lipid peroxidation secondary damage after SCI plays and important role, and early application after spinal cord injury promoted radical scavengers, reducing the production of MDA increased SOD activity (Zhao et al, 2011;Kumar et al, 2011;Vinit, 2012;Krause et al, 2012). Blood flow changes after SCI, and extensive infiltration of inflammatory cells also result in a large amount of oxygen free radicals (Donnelly et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With MDA significantly increased after SCI, SOD significantly reduced, suggesting that lipid peroxidation in damage localization increased, it is also the result of increased free radicals (Gonzalez et al, 2003;Wang et al, 2009;Hakan et al, 2011). Free radicals and lipid peroxidation secondary damage after SCI plays and important role, and early application after spinal cord injury promoted radical scavengers, reducing the production of MDA increased SOD activity (Zhao et al, 2011;Kumar et al, 2011;Vinit, 2012;Krause et al, 2012). Blood flow changes after SCI, and extensive infiltration of inflammatory cells also result in a large amount of oxygen free radicals (Donnelly et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…SCI pathophysiology is very complex, involving histopathological, electrophysiological and chemical changes in affected cells and tissues (Gonzalez et al, 2003;Wang et al, 2009;Hakan et al, 2011;Zhang et al, 2012;Lang et al, 2012;Atılgan, 2012). In order to clarify the complex mechanisms involved in SCI, and evaluate potential interventions in the treatment of SCI, it is important to use a model of SCI model which has high reliability and replicability (Zhao et al, 2011;Kumar et al, 2011;Vinit, 2012). A variety of pathogenic factors can cause spinal cord injury, resulting in a range of pathological changes and dysfunctions (Vinit, 2012;Krause et al, 2012;Wijesuriya et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Postmarketing surveillance data collected from 1426 persons who received Fasudil in Japan revealed that only 3.8% experienced adverse effects; hemorrhage was the most common, occurring in 1.7%, with hypotension observed in only one person (0.07%) . In a trial comparing fasudil with the calcium channel blocker nimodipine for treatment of cerebral vasospasm, fasudil was associated with significantly better clinical outcomes and no serious adverse events, including no episodes of hypotension requiring drug cessation (Zhao et al, 2011). A recent meta-analysis of the efficacy and safety of fasudil for the treatment of cerebral vasospasm in persons with subarachnoid hemorrhage found no increase in adverse events with fasudil use .…”
Section: Potential Toxicities Of Rho-associated Coiled-coil Formmentioning
confidence: 99%
“…Zhao et al, conducted a randomized, open trial to compare the efficacy and safety of vasudil compared with nimodipine. The results of this study suggested that fasudil was equally safe and eequally or more effective than nimodipine for the prevention of cerebral vasospasm and subsuquent ischemic injury in patients undergoing surgery for SAH [108]. Nakamura et al, showed that the selective intra-arterial infusion of fasudil was signifficantly effective for the treatment of delayed vasospasm and more beneficial than the nonselective treatment [109].…”
Section: Inhibitors Of Rho-associated Kinase (Rock)mentioning
confidence: 68%